Surveying Christian Beliefs and Religious Debates in Post-War Britain - Clements, Ben (SpringerLink Bücher, 2016)
Clements provides a detailed study of religious beliefs in British society, using a broad range of opinion poll and social survey data. Examining public opinion on religious-secular issues, this book provides a rich analysis of the belief and attitudes of social groups over time.